Exploring Accountability in School Counseling: Research Trends, Applied Models, and Implications for Practice in Indonesia - Isrofin, Binti; Taufiq, Agus; Ahman, Ahman; Yustiana, Yusi Riksa; Dudin, Dudin (KONSELOR, 2024)
The present focus of school counselling accountability extends beyond merely tallying activities and time invested by counsellors; it necessitates that school counsellors implement results-oriented and evidence-based methods. This study is to examine the literature about trends, models, and barriers faced by counsellors in the implementation of accountability practices. This study employs a Narrative literature review and Bibliometric analysis covering the period from 2003 to 2023, analysed using Vosviewer. The research findings indicate that the literature on accountability in school counselling is intricately linked to program evaluation, data-driven decision-making, and stakeholder collaboration, all aimed at enhancing the efficacy of counselling services in educational institutions and ultimately fostering student success. The findings of the narrative literature review elucidate models that serve as references for school counsellors in implementing accountability practices, specifically data-driven decision-making, the transformative individual school counselling model, MEASURE, the evidence-based model, and the IDEAS model. Additionally, researchers identified accountability barriers stemming from both internal and external factors affecting school counsellors.These findings may serve as a foundation for future study aimed at establishing a data-driven approach to enhance school counsellor accountability.